The NeoPIns study: a step towards a rational use of antibiotics in early-onset sepsis in term neonates - Vinclair, Camille; Timsit, Jean-François; Bouadma, Lila (Journal of Emergency and Critical Care Medicine, 2017)
We read with interest the results of the NeoPIns trial, published this year in The Lancet by Stocker and colleagues and assessing the effect of a procalcitonin (PCT) guided algorithm in early-onset neonatal sepsis in term infants (1).